Establishing a benthic macrofaunal baseline for the sandy shoreline ecosystem within the Gulf Islands National Seashore in response to the DwH oil spill - Rakocinski, Chet F.; LeCroy, Sara E.; VanderKooy, Kathy E.; Heard, Richard W. (Frontiers in Environmental Science, 2023)
Sandy shorelines present a first line of defense against oil spills within the coastal zone of the northern Gulf of Mexico. In May 2010, immediately following the DwH oil spill but before any impacts occurred, we conducted a rapid survey of the sandy shoreline benthic macrofauna from throughout the National Park Service - Gulf Islands National Seashore in Mississippi and Florida districts. To characterize pre-spill macrofaunal assemblages, we sampled seven barrier island or peninsular areas representing nine exposed and 12 protected shoreline sites. A comparable benthic macrofaunal inventory conducted using a parallel study design had been done 17 years earlier in 1993. The primary objective of this study was to examine and compare hierarchical spatiotemporal scales of variation in macrofaunal assemblages within the combined commensurate 1993 and 2010 macrofaunal GINS dataset. We hypothesized that the 1993 GINS macrofaunal inventory still provides a valid baseline, despite multiple large storm disturbances within the intervening 17-year period. Moreover, we expected the relative importance of macrofaunal variability in assemblage structure to vary across hierarchical spatiotemporal scales. A Hierarchical Implicit Nested Mixed Model PERMANOVA using Type 1 sequential Sum of Squares quantified variation components for scales represented by the main factors: Station > Shore Side > Site > Habitat > District > Year. The Year main factor had the smallest effect on macrofaunal variation, confirming that the 1993 GINS macrofaunal inventory can serve as the foundation of a robust macrofaunal baseline for the GINS. A Hierarchical Nested Mixed Model PERMANOVA using Type 1 sequential Sum of Squares (SS) provided a complementary perspective for partitioning effects among nested factors and their interactions. Definitive macrofaunal variation was expressed for all combinations of two levels for each of the three spatially nested fixed factors, District, Side, and Habitat. Variation in macrofaunal dissimilarity for combined levels of fixed factors reflected corresponding differences in relative abundances of major macrofaunal taxa. The use of benthic macrofaunal assemblages as indicators would fulfill the need to focus on cumulative effects of oil spills and should be eminently more tractable when responses and impacts are placed on commensurate scales.